The Influence of Brand Experience, Brand Personality, Brand Trust, And Customer Satisfaction In Building Customer Loyalty: Case Study On BANGTAN SONYEONDAN FANS (Journal of Business and Management, 2022)
Bangtan Sonyeondan or the international name BTS is the leading K-Pop boy band by the number of their fans. ARMY “Adorable Representative M.C of Youth” social network for those who are willing to BTS fans. The massive phenomenon of ARMY who are willing to buy BTS merchandise resulting ARMY start to experience that BTS giving their memories of happiness by buying their merchandise. They learn to trust, match personalities, satisfy as consumer, and make them loyal to BTS.This research analyzed the relationship of brand experience, brand personality, brand trust, and customer satisfaction to customer loyalty to ARMY.The results also be helpful for recommendations and references for companies in the music sector and BTS, regarding the benefits and relationships of the five variables. Using quantitative approach by collecting data through questionnaire and use purposive sampling with a result of 232 respondents. Analyzing data using descriptive analysis and PLS-SEM. This study shows that brand experience has a significant effect on brand personality, brand trust, and customer satisfaction. Brand trust and customer satisfaction can significantly affect customer loyalty. The mediating result states that customer satisfaction can fully mediate brand experience to customer loyalty, while brand trust and brand personality partially mediate.Keywords: BTS, ARMY, Merchandise, Quantitative, PLS-SEM, Brand Experience, Brand Personality, Brand Trust, Customer Satisfaction, Customer Loyalty.